State Legislative Support for Parks - Judy Kruger; Tina Lankford; Tom schmid (SAGE Publishing, 2010)
Background Parks are important venues that can encourage population-level physical activity, and policy legislation can facilitate or discourage physical activity and other park uses, depending on the type and level of support. This study aims to summarize the status and content of state-level park-related legislation. Methods We searched for eligible legislation from 2001-2007 in two data sources, CDC's Nutrition, Physical Activity and Obesity Legislative Database and Lexis-Nexis, using the key words conservation, growth management/land use, parks, recreation, preservation, path, green space, or open space. State legislation was categorized into seven broad topic areas and analyzed by number introduced and passed (enacted as law), by state and category. Results States varied in the number and type of park-related legislation introduced and passed. Common categories of introduced park-related state legislation were preservation or conservation (n = 26, 9 passed), funding (n = 43, 10 passed), creation or acquisition of park land (n = 53, 9 passed), safety and liability (n = 34, 5 passed), accessibility (n = 20, 2 passed), outreach (n = 15, 2 passed), and outdoor activities (n = 13, 2 passed). Conclusion During 2001 to 2007, 19% of park-related state legislation was enacted. Research on legislative policy is an emerging field, and more information on the content of park-related legislation could assist states in their efforts to promote physical activity in park venues.